2022
DOI: 10.56261/built.v19.246242
|View full text |Cite
|
Sign up to set email alerts
|

Is 1-Minute of Nature Enough? : Durations of Nature during Walking and Attention Restoration

Abstract: Walking in nature provides several health benefits including restoring attention capacity. However, researchers do not know the extent to which the duration of green exercise affects attention restoration. This lack of evidence prevents designers and planners from effectively providing this nature’s co-benefit. This study tested the extent to which a view of nature and durations of nature while walking may impact attention restoration. 79 participants completed attentionally demanding tasks and walked on a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In other words, how much time should we spend in nature to gain optimal benefits? While some research has found that spending one to five minutes with nature can provide the highest mental health benefits [ 39 , 40 ], others have indicated that 10 min was sufficient to restore attention and help people recover from stress [ 36 , 38 ]. Another study found that in a range of 0–80 min, 20–30 min of nature exposure provided the best benefits [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, how much time should we spend in nature to gain optimal benefits? While some research has found that spending one to five minutes with nature can provide the highest mental health benefits [ 39 , 40 ], others have indicated that 10 min was sufficient to restore attention and help people recover from stress [ 36 , 38 ]. Another study found that in a range of 0–80 min, 20–30 min of nature exposure provided the best benefits [ 41 ].…”
Section: Introductionmentioning
confidence: 99%